The Digital Transformation in the Economic Growth of Indonesian Sharia Bank Services - Erna May Wulandari; Maya Indriastuti (University of Darussalam Gontor, 2023)
This study aims to analyze economic growth and digital banking transformation as seen fromthe Indonesian Islamic banking industry. The development of Islamic finance provides a newperspective on the study of the relationship between economic growth and the transformationof the digital banking industry. Digital banking transformation is an important issue intoday's banking industry. The disruption of the digital era has changed the way a personconducts transactions in business. The dynamics of understanding the use of technology infinancial literacy is still low so that it can encourage economic growth and improve people'swelfare. In addition, there are very few studies on the growth finance nexus that can be viewedfrom an Islamic finance perspective, especially in Indonesia. The method in this study uses aliterature study that is used in writing this article in the form of an assessment of researchjournals, dissertations, studies, and relevant mass media. This study uses qualitative data andsecondary data sources. Theimplications of this research only focus on Islamic banking, makingdigital transformation a priority strategy in efforts to increase economic growth in Indonesia.So, this research contributes to the discussion of economic growth that can be influenced bydigital transformation in the use of digital services in Islamic banks in Indonesia. Keywords: Economic Growth, Digital Transformation, Development of Islamic Finance, Indonesian Islamic Bank